Patients' reported experiences and outcomes following surgical excision of lower limb osteomyelitis and microvascular free tissue reconstruction under 'awake' epidural anaesthesia and sedation. Issue 4 (August 2021) - Galitzine, Svetlana; Wilson, Katy; Edington, Magdalena; Burumdayal, Amisha; McNally, Martin
Abstract: Background: Orthoplastic operations for lower limb osteomyelitis (LLOM) involving microvascular free tissue reconstructions ("free-flaps") are usually performed under general anaesthesia (GA), with or without epidural anaesthesia (EA) due to concerns about the discomfort associated with prolonged surgery. However, our clinical experience supports "awake" epidural anaesthesia with sedation (EA + Sed) rather than EA + GA as a technique of choice for this type of surgery. Methods: We used a standardised postoperative questionnaire to formally assess the experiences and outcomes for 50 patients who underwent free-flaps for LLOM under EA + Sed. Findings: The mean duration of surgery was 522 min (8.7 h), range 240–875 min. There were no ITU admissions or flap failures. Postoperatively, fifty patients completed a standardised questionnaire about their experiences before the operation, in the anaesthetic room and theatre. 80% were aware of the procedure at least "some of the time". 72.5% patients and 75% respectively, did not have any concerns in the anaesthetic room and theatre. Concerns expressed by the remaining patients were manageable. 97.5% of those patients who recalled their operation reported their overall experience as "comfortable" or "very comfortable". 92% of respondents had undergone previous lower limb surgery under GA ± EA. In this subgroup, 91.3% reported the recovery after EA + Sed as "quicker" than GA, and 89.4% reported their experience with EA + Sed as "better". All fifty patients (100%) were "satisfied" or "very satisfied" with their experience and all but one (98%) would recommend this technique to others. Conclusions: Our study showed that despite prolonged duration, the patients' reported experiences and outcomes were excellent when EA + Sed was used for orthoplastic operations involving free-flaps for LLOM. We recommend EA + Sed as the anaesthetic technique of choice for such patients. Highlights: Orthoplastic operations for lower limb osteomyelitis (LLOM) involving microvascular free tissue reconstructions ("free-flaps") are usually performed under general anaesthesia (GA) with or without epidural anaesthesia (EA), due to concerns about the discomfort associated with prolonged surgery. EA without GA ensures reliable analgesia and provides stable physiology, thus optimising the perfusion of "free flaps". EA alone avoids vasoconstriction due to inadequate pain relief, hypoxaemia, and surges of blood pressure. Our study showed that despite prolonged duration, the patients' reported experiences and outcomes were excellent under EA with Sedation.